Myofilamental integrity of the myometrium due to cold ischaemia stress during autotransplantation in the experimental sheep model - Bálint Farkas; Katalin Türmer; Martin Rozanovic; Kálmán Kovács; József Bódis; Gábor Jancsó; Gábor Fazekas; Dávid Szatmári (PLoS ONE, 2025)
Uterine transplantation is currently the only solution that enables women with absolute uterine factor infertility to become pregnant and give birth to a child. In the preparatory phase of a human uterus transplantation, the sheep is the most recommended species. Cold ischaemia, i.e., a period of reduced or absent blood flow at cold conditions, can significantly impair the function of the transplanted organ. Cold ischaemia impairs smooth muscle function in general and reduces smooth muscle contractile activity. However, it seems to provide some protection against cold storage. Our main goal was to investigate the molecular mechanisms leading to reversible changes in myometrial myofilaments and to distinguish these from permanent changes, which was supported by histological imaging of uterine samples. Using fluorescence spectroscopy, we investigated important interactions between major components of smooth muscle such as actin and tissue-specific actin-binding proteins. We characterized functional changes by denaturation sensitivity and protein-protein interactions under low and high salt conditions by intrinsic tryptophan, Alexa488-phalloidin and eosin fluorescence emission spectroscopy assays. Our results suggest that short-term cold ischaemia causes minor disruption of muscle cells. The protein extracts of myometrium contained large amounts of actin, which was present in soluble complexes with actin-binding proteins after ischaemic stress. The results indicate that the contractile filament system underwent molecular stabilization and reassembly due to ischaemic stress and that the actin monomers were unable to form polymers due to increased heterologous protein-protein interactions. The content of necrotic proteins cannot be detected after brief ischaemia, but eosin selectively binds to large proteins (caldesmon, myosin chains, tropomyosin) and protein complexes. Based on these results, we can assume that short-term preservation of cold ischaemia in uterine transplantation reduces the risk of using it in clinical trials for complete myometrial recovery after reperfusion.